Disentangling rodent behaviors to improve automated behavior recognition - Van Dam, Elsbeth A.; Noldus, Lucas P. J. J.; Van Gerven, Marcel A. J. (Frontiers in Neuroscience, 2023)
Automated observation and analysis of behavior is important to facilitate progress in many fields of science. Recent developments in deep learning have enabled progress in object detection and tracking, but rodent behavior recognition struggles to exceed 75-80% accuracy for ethologically relevant behaviors. We investigate the main reasons why and distinguish three aspects of behavior dynamics that are difficult to automate. We isolate these aspects in an artificial dataset and reproduce effects with the state-of-the-art behavior recognition models. Having an endless amount of labeled training data with minimal input noise will enable research to optimize behavior recognition architectures and get closer to human-like recognition performance for behaviors with challenging dynamics.